Molecular phylogeny of fig wasp pollinators (Agaonidae, Hymenoptera) of Ficus section Galoglychia - (:unkn) unknown (My University, 2007)
The obligate mutualism between fig trees and their fig wasp pollinators, together with the general tendency for each host species to be pollinated by one fig wasp species, led to the hypothesis that these two lineages have cospeciated. The pollinators of African figs of section Galoglychia form a diverse group of genera whose species seem to be less constrained to a specific host than other pollinating fig wasp genera. Various authors have suggested remarkably different phylogenetic relationships between the seven genera associated with section Galoglychia. These uncertainties concerning the classification make it difficult to understand the historical patterns of association between these wasps and their hosts. The phylogenetic tree for the pollinators was reconstructed with 28S, COI and ITS2 DNA sequence data and compared with morphological classification of the hosts. Pollinator genera were monophyletic in all analyses. However, the relative position of some genera remains unresolved. Investigation of host−fig association suggests that there have been frequent host jumps between host subsections. This indicates that cospeciation between fig trees and fig wasps is not as stringent as previously assumed. In addition, pollinators of the genus Alfonsiella associated with three host figs (Ficus craterostoma, F. stuhlmannii and F. petersii) are morphologically very similar in South Africa. We investigated the possibility that these pollinators form a complex of species with host-based genetic differentiation. Molecular analyses supported the distinction of the pollinator of F. craterostoma as a good species, but the pollinators of F. stuhlmannii and F. petersii clustered within the same clade, suggesting that these two host species share a single pollinator, Alfonsiella binghami. Based on both molecular data and morphological re-evaluation, a new Alfonsiella species is described, Alfonsiella pipithiensis sp. nov., which is the pollinator of F. craterost
Keywords: African Research